Regional patterns of inflation persistence in Italy - Guido Ascari; Andrea Vaona (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2007)
Regional patterns of inflation persistence have received attention only at a very coarse level of territorial disaggregation, that of EMU member states. However economic disparities within EMU member states are an equally important policy issue. This paper considers a country with a large regional divide, i.e., Italy, at a fine level of territorial disaggregation (NUTS3). Our results show that economically backward regions display greater inflation persistence. Moreover, we show that higher persistence is linked to a lower degree of competitiveness in the retail sector.
Keywords: 330; Inflation; Inflationsrate; Verbraucherpreisindex; Einzelhandel; Wettbewerb; Regionale Disparität; Italien